Gender and labor: interdisciplinary analysis of the labor market in caxias do sul in the 2000’s - Pietra Méndez, Natalia (2010)
The article examines gender relationships in the formal labor market in the 2000's in the city of Caxias do Sul. The objective is to discuss the effects of technical and productive changes in the world of labor, and possible repercussions on the profile of jobs and workers. The research uses as its primary source data available in the Relação Anual de Informações Sociais (RAIS), administered by the Ministry of Labor, Brazil. This paper is located within an interdisciplinary field of human sciences and the survey data and indicators treatment is an exercise of statistical approach to the applied and social sciences. The methodology uses the data as evidence to consider multiple social relations among workers: monitoring changes in wages, the sectors of activity, and types of occupation. One can establish a relation with variables that problematize the profile of the workers as relations of gender and education level. Changes were observed in the profiles of the workers. The rise of education, especially for males, is a major factor in this period. There was an increase in female participation in traditionally male sectors of occupation and the solidification of female leadership in some occupations. Although there are transits and movements, gender relations remain as an element of segregation in the workplace.